Oksidentalisme ; Membuka Kedok Imperalisme Barat: (Studi Politik Imperalisme Belanda Abad 19 dan Awal Abad 20 di Jawa Melalui Kajian Sejarah) - izza, yogi prana (At-Tuhfah : Jurnal Studi Keislaman, 2017)
Occidentalism is the opposite of orientalism. If Orientalism serves as a theory of knowledge that is used to study the eastern world (Islam), then the reverse is occidentalism is used to study the Western world. One of the initiators of Occidentalism figure is Hasan Hanafi. Through his Occidentalism theory, this paper seeks to unmask imperialism Dutch politics in Java in the 19th century and the beginning of 20. The result is a political culture that is used Dutch ancient times, same the patterns with contemporary politics in the present era. Thus, it is time, the reality of contemporary addressed wisely. As the purpose of Occidentalism’s Hassan Hanafi is to awaken people to the project called "atturast wa at-tajdid" (Heritage Civilization and Renewal) and the reality of the present (al-waqi ') can be addressed wisely by doing the reconstruction of the heritage of ancient civilizations (at-turast al-Qodim), as well as the position of al-ana confirmation before Western culture (al-Akhar)